Religious musical practice in Brazil and Portugal in the second half of eighteenth century: parallels and basis for the vocal interpretation of the music of José Joaquim Emerico Lobo de Mesquita (Per Musi, 2011)
In this essay we intend to investigate the similarities in style between the music of the composer from Minas Gerais José Joaquim Emerico Lobo de Mesquita, particularly in the soprano solo of his Mass in E flat, and the soprano solo of a Mass for five voices by David Perez and the first movement of the motet Care Deus si respiro, for soprano solo and strings, by Niccoló Jommelli, Italian composers of the Neapolitan school who worked for the Portuguese court in the second half of the 18th century.